Screening of TACE Peptide Inhibitors from Phage Display Peptide Library - 黄巍 李凌波 韩玲 杨渝珍 (Journal of Huazhong University of Science and Technology. Medical sciences, 2005)
Summary： To obtain the recombinant tumor necrosis factor-α converting enzyme （TACE） ectodomain and use it as a selective molecule for the screening of TACE peptide inhibitors, the cDNA coding catalytic domain （TS00） and full-length ectodomain （T1300） of TACE were amplified by RT-PCR, and the expres.sion plasmids were constructed by inserting T800 and T1300 into plasmid pET-28a and pET-28c respectively. The recombinant TS00 and T1300 were induced by IPTG, and SDS-PAGE and Western blotting analysis results revealed that TS00 and T1300 were highly expressed in the form of inclusion body. After Ni^2＋-NTA resin affinity chromatography, the recombinant proreins were used in the screening of TACE-binding peptides from phage display peptide library respectively. After 4 rounds of biopanning, the positive phage clones were analyzed by ELISA, competitive inhibition assay and DNA sequencing. A common amino acid sequence （TRWLVYFSRPYLVAT） was found and synthesized. The synthetic peptide could inhibit the TNF-α release from LPS-stimulated human peripheral blood mononuclear cells （PBMC） up to 60.3%. FACS analysis revealed that the peptide mediated the accumulation of TNF-α on the cell surface. These results demonstrate that the TACE binding peptide is an effective antagonist of TACE.